Correlation between Physical Fitness Components and Academic Achievement in Elementary School Students - Tisnasari Hafsah; Nurul Uyun; Reni Farenia (Althea Medical Journal, 2018)
Background: Physical fitness is a degree of health status as a basic physical condition of someone to perform daily activity. Elementary school students should have a good physical fitness to obtain satisfactory academic achievement. The purpose of this study was to examine the correlation between physical fitness and academic achievement. Methods: This study used an observational analytical method with cross-sectional design, conducted from September−October 2013, using total sampling method. There were 82 students of the 4th−6th- grade from Cikeruh 2 elementary school at Jatinangor. The school was chosen by random selection. The physical fitness assessment in this study consisted of step test to measure cardiorespiratory endurance, body mass index (BMI) for body composition, push-up for muscular strength and sit-up for muscular flexibility. Academic achievement was collected from the last examination result. Each component of physical fitness test results were converted to a score and then categorized.Results: Most students (74.4%) had fair physical fitness, boys 68.3%, and girls 80.5%. No correlation was found between physical fitness and academic achievement (p=0.432 and r=0.162).Conclusions: There is no significant correlation between physical fitness and academic achievement.